(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2016)
The work began with an analysis of reading and writing skills based on a diagnostic test of reading comprehension and textual production that assessed the students’ level through the interpretation of comic strips using activities involving opinion, comprehension, vocabulary knowledge, interpretation of terms, idioms and expressions, summarizing, concept development, text creation, use of punctuation marks, and textual coherence. It continued with the creation and implementation of twelve workshops that make up the teaching proposal, with topics and processes designed based on the results of this initial assessment.